2022
DOI: 10.1097/icl.0000000000000899
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Response to Scleral Contact Lens Wear in Keratoconus

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Iqbal et al 23 showed that a scleral lens with a central lens thickness of 200 to 400 mm did not induce corneal edema after 6 hr of contact lens wear in patients with keratoconus. Cagliari et al 24 followed up with 22 patients with keratoconus who were fitted with scleral lenses for 90 days. They showed that there was no significant change in endothelial morphology and pachymetry values over time.…”
Section: Discussionmentioning
confidence: 99%
“…Iqbal et al 23 showed that a scleral lens with a central lens thickness of 200 to 400 mm did not induce corneal edema after 6 hr of contact lens wear in patients with keratoconus. Cagliari et al 24 followed up with 22 patients with keratoconus who were fitted with scleral lenses for 90 days. They showed that there was no significant change in endothelial morphology and pachymetry values over time.…”
Section: Discussionmentioning
confidence: 99%
“…16 In fact, they were considered the gold standard for patients with advanced KC, 16–18 but numerous studies reported the benefits of SL versus RGPCL for advanced corneal irregularities, achieving greater comfort, centration, stability, and providing good VA and long-term safety and efficacy. 19–25 The latter is discussed by Fuller et al showing an excellent long-term safety and efficacy of SL in the visual rehabilitation in subjects with KC, therefore achieving an improvement in VA. 21 Cagliari et al 22 also evaluated safety and highlighted that the daily use of SL in KC patients was not associated with adverse effects on the cornea or endothelium over a 90-day period and they did not find a progression of the disease. Vincent et al 25 stated that SL may provide exceptional VA outcomes in patients with complex corneal shapes that otherwise would not be achieved with a smaller diameter rigid lens.…”
Section: Discussionmentioning
confidence: 99%
“…28,33 Although for KC, in the initial stages, the best options are HCL and STCL, 16,30,32,34 it has been reported that in more advanced stages of the disease, the best VA is only achieved with RGPCL or SL. [16][17][18][19][20][21][22][23][24]27,28 SL allow correcting the ametropia and HOA that these patients usually present, 27 and although some authors wage for corneo-scleral modality, 20,27 others defend full scleral modality, 16,26 and have also reported successful improvements with MSCL. 10,14…”
Section: Keratoconusmentioning
confidence: 99%
“…[ 28 ] In a study done by Cagliari et al ., variables related to endothelial morphology and pachymetry values did not change significantly over time from the above study. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%